- #1

- 1

- 0

- Thread starter nidak
- Start date

- #1

- 1

- 0

- #2

- 1,056

- 0

Given any primitive root, it follows that r^(p-1)==1 Mod p, **but not for any lesser power.** But (p-l)/3 =u, is an integer less than p-1, and it follows that:

(a^3)^u ==1 Mod p.

(a^3)^u ==1 Mod p.

Last edited:

- #3

- 41

- 0

Look up Henzel's lemma in Lang or Milne's online course note. It is relavant.

- #4

- 291

- 0

No need to use Hensel's lemma, what robert did is perfect.Look up Henzel's lemma in Lang or Milne's online course note. It is relavant.

- Last Post

- Replies
- 5

- Views
- 9K

- Last Post

- Replies
- 10

- Views
- 4K

- Last Post

- Replies
- 2

- Views
- 5K

- Last Post

- Replies
- 7

- Views
- 3K

- Last Post

- Replies
- 5

- Views
- 2K

- Last Post

- Replies
- 4

- Views
- 2K

- Last Post

- Replies
- 4

- Views
- 6K

- Last Post

- Replies
- 8

- Views
- 6K

- Last Post

- Replies
- 2

- Views
- 5K

- Replies
- 4

- Views
- 3K